That savage gaze : wolves in the nineteenth-century Russian imagination - Helfant, Ian M. (Unknown nineteenth century., 2018)
Imperial Russia's large wolf populations were demonized, persecuted, tormented, and sometimes admired. That Savage Gaze explores the significance of wolves in pre-revolutionary Russia utilizing the perspectives of cultural studies, ecocriticism, and human-animal studies.